2013
DOI: 10.5812/traumamon.8322
|View full text |Cite
|
Sign up to set email alerts
|

Orthopedic Injuries Following the East Azerbaijan Earthquake

Abstract: BackgroundEvaluating demographic characteristics, distribution and types of orthopedic injuries following major earthquakes may be helpful in future planning for disasters.ObjectivesThis study aimed to analyze data from trauma patients with extremity injury resulting from the earthquakes of East Azerbaijan, Iran.Patients and MethodsMedical records of 686 patients admitted to Shohada hospital, Trauma Center of Tabriz University of Medical Sciences were reviewed. There were 200 patients with extremity injury ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
1
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(11 citation statements)
references
References 12 publications
2
7
1
1
Order By: Relevance
“…Despite the fact that in different studies the most prevalent fractures were femur and hip injuries ( 8 , 12 , 13 ), the most prevalent injury in our study was the fracture of distal radius. Double fracture (Tibia and Fibula fractures or Radius and Ulna fractures at the same time) is an injury that only occurs following high-energy traumas and in most cases, it is accompanied by severe soft tissue injuries.…”
Section: Discussioncontrasting
confidence: 61%
“…Despite the fact that in different studies the most prevalent fractures were femur and hip injuries ( 8 , 12 , 13 ), the most prevalent injury in our study was the fracture of distal radius. Double fracture (Tibia and Fibula fractures or Radius and Ulna fractures at the same time) is an injury that only occurs following high-energy traumas and in most cases, it is accompanied by severe soft tissue injuries.…”
Section: Discussioncontrasting
confidence: 61%
“…Most of work put the upper limb at risk of injury due to the need of hand skills or need of muscular power or even when a person exposed to trauma to a lower limb, like fall or RTA, he would try to protect himself or hold the body by upper limb. Other studies done; in India (2011) [18] East Azerbaijan, (2013) [19] showed the same finding of predominated injuries of extremities and lower prevalent of pelvic injuries. The results of this study showed that road traffic accident made up 15% from all types of trauma.…”
Section: Discussionsupporting
confidence: 62%
“…With the exception of one article, closed fractures resulted more frequently than open fractures. [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] Given the state of the collected data, it is impossible to establish if there is any statistically significant prevalence of a type of fracture or of an anatomical region affected among trauma patients resulting from any given earthquake. This contradicts the understanding that upper and lower extremity injuries are more frequent during nightly/early morning than daytime earthquakes, respectively 6,21 (Table 2).…”
Section: Study Overviewmentioning
confidence: 99%
“…With the exception of two studies, all articles reported that fractures affected more lower than upper limbs. [6][7][8][9][10][11][12][13][14][15]17,[19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] No association was found between short time-to-treatment and lower number of complications; amputation rate; or use of EF rather than ORIF. Qualitatively, it is possible to define that there are more open fractures during daytime hours than at night.…”
Section: Study Overviewmentioning
confidence: 99%